PENGARUH SALES PROMOTION, EWOM, CONTENT MARKETING TERHADAP ATTITUDE DAN PURCHASE INTENTION PRODUK SIAP MINUM TOMORO COFFEE DI JAKARTA - Andika Bagus Nugroho; Setyo Ferry Wibowo; Rizka Zakiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The growth of information technology and the internet has dramatically changed the way individuals search, choose, and interact with brands or products. This study aims to analyze the influence of sales promotion, e-WOM, and content marketing on the attitude and purchase intention of Tomoro Coffee ready-to-drink products in Jakarta. This study used a survey method, while the data collection technique was through an online questionnaire of 200 Tomoro Coffee consumer respondents in the DKI Jakarta area. Data analysis was conducted using quantitative methods with AMOS software. The results showed that sales promotion, electronic word of mouth, and content marketing had a positif and significant effect on attitude and purchase intention. These findings summarize how sales promotions such as coupons, rebates, and special prices attract attention through the urgency of limited offers, build interest with high perceived value, trigger desire through stimulus, and drive the process towards direct purchase intention. On the other hand, e-WOM provides social validation at the attention stage through authentic reviews, strengthens interest and desire with trust, and encourages the formation of positif attitudes. In addition, shared content marketing leads to action through high engagement that forms a favorable attitude towards purchase intention. This research contributes to the development of theory in the field of digital marketing, particularly for marketers, entrepreneurs, and policymakers in developing effective and efficient digital marketing communication strategies.